Processos de ensino-aprendizagem dialógico-problematizadores mediados por recursos educacionais abertos (REA) na disciplina de matemática nos anos finais do ensino fundamental - Cechin, Lucas de Lima (2022)
This thesis, through an action-research, it aimed to investigate and analyze the contributions and collaborations of the dialogical-problematizing teaching-learning process mediated by Open Educational Resources (OER) in remote Mathematics classes in the final years of elementary school. It refers to research associated with the line of research on Educational Public Policies, Educational Practices and their Interfaces in the Graduate Program in Education at the Federal University of Santa Maria (UFSM). In order to reflect on a dialogicproblematizing education, I’ve searched for Paulo Freire's bibliographies throughout the period in which this study was carried out. Allied to Freire's educational principles of dialogue and questioning, the system advised by Kemmis and MCTaggart based on three matrices stood out: Dialogic-Problematizing Matrix (MDP), Thematic-Organizing Matrix (MTO) and ThematicAnalytical Matrix (MTA). The methodological approach was based on these three matrices, starting with the delimitation, organization and analysis of data in order to structure a thematic concern of an action research. In view of the social isolation caused by the pandemic caused by the new coronavirus, the study environment initially took place remotely, seeking to meet the standards of the Municipality of Education (SMED), including the remote emergency curriculum. It was concluded that the teaching-learning processes in remote classes mediated by OER based on a dialogic-problematizing education strengthen contextualized knowledge when the cultivation of participation embraces all the cultures involved.